Systematic Study: The Child with Recurrent Infections - Arnoldo Quezada (Highlights on Medicine and Medical Research Vol. 4, 2021)
The child with recurrent infections proposes a diagnostic challenge to discard an immunodeficiency. There is no definitive consensus to determine the number of infections that can be considered normal. Children with recurrent infections can be included in four basic types of diagnostic categories: probably normal child, allergic child, children with chronic disease, and immunodeficient child. Different warning signs have been developed to guide the appropriate detection of children with primary immunodeficiency diseases (PID). The value of a detailed clinical history and an exhaustive physical examination, as well as the study with initial laboratory tests are discussed. The last report of the expert committee of the International Union of Immunology Societies has proposed the name of Inborn Errors of Immunity for PIDs. A smartphone application is available for clinicians and students that facilitates the diagnosis of PID. Some PID may be suspected as more probable depending on the infectious agent.